Aplication of Foot Massage Therapy to Reduce Blood Pressure in Hypertension Sufferers: A Systematic Review (Comprehensive Health Care, 2024)
Hypertension is a condition in which there is an increase in systolic blood pressure above the normal limit, namely more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Objective: This systematic review aims to examine the effectiveness of foot massage interventions to reduce blood pressure in hypertensive patients. which includes intervention models, measurement instruments, and evaluating the impact and effectiveness of foot massage interventions on reducing blood pressure. Method: used. Searches in this systematic review are several international data bases, namely Proquest, Ebsco, PubMed, Taylor, Cohrane, and secondary research (Gray literature) with a time span of 2018 to 2023 (10 years). Results: After reviewing all the articles, it was found that foot massage can reduce both systolic and diastolic blood pressure. The intervention model regarding Foot Massage varies in each study regarding the treatment of blood pressure in hypertensive patients and the most common is Foot Massage. The most widely used instrument for measuring blood pressure is the Sphygmomanometer. The results of evaluating the impact and effectiveness of the intervention show that Foot Massage is able to reduce both systolic and diastolic blood pressure. Likewise, the results of a systematic review show that foot massage is able to reduce both systolic and diastolic blood pressure. Conclusion: Hypertension patients who underwent foot massage therapy for approximately 30 minutes, at all reflex points on both feet, once every two weeks, for 4 weeks to 10 consecutive weeks experienced a significant reduction in the level of fatigue intensity. The time for measuring results should be carried out 24 hours after the intervention or serially according to the session carried out and using a certified and experienced therapist